2021
DOI: 10.20452/pamw.16120
|View full text |Cite
|
Sign up to set email alerts
|

Rapid pharmacological cardioversion of recent-onset atrial fibrillation using antazoline in elderly patients

Abstract: What's new?Our study conducted on 334 patients suggests that intravenous antazoline is similarly effective and safe for patients ≥75 and <75 years old in terms of conversion rates to sinus rhythm and risk of hospitalization due to adverse events. Therefore antazoline may be a viable option for the pharmacological cardioversion of recent-onset atrial fibrillation performed in the emergency department in the elderly while other fast acting agents may be contraindicated or simply not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In the earlier CANT I study [23] and the current high-volume CANT II study [13], antazoline has been shown to have comparable efficacy to propafenone and superior efficacy to amiodarone in terms of the rate of rhythm conversion. Also, Farkowski et al found that antazoline is characterized by even better efficacy than propafenone [24], and its efficacy extended to the elderly population [25]. What is more, none of the above-mentioned results indicated serious adverse events related to the use of antazoline in comparison to other AADs.…”
Section: Discussionmentioning
confidence: 99%
“…In the earlier CANT I study [23] and the current high-volume CANT II study [13], antazoline has been shown to have comparable efficacy to propafenone and superior efficacy to amiodarone in terms of the rate of rhythm conversion. Also, Farkowski et al found that antazoline is characterized by even better efficacy than propafenone [24], and its efficacy extended to the elderly population [25]. What is more, none of the above-mentioned results indicated serious adverse events related to the use of antazoline in comparison to other AADs.…”
Section: Discussionmentioning
confidence: 99%
“…However, during the last decade, new data have emerged showing that antazoline also has an antiarrhythmic activity with quinidine-like properties and is effective in the termination of paroxysmal atrial fibrillation (AF) [ 1 , 2 , 3 , 4 ]. In addition to the fact that antazoline quickly and effectively terminates AF, it is also safe in the elderly and in the patients with stable coronary artery disease [ 5 , 6 ]. These effects of antazoline’s use in cardiology and emergency medicine have been recently described in a comprehensive review published by [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard for the exclusion of LAAT is transesophageal echocardiography (TOE) [9,10]. However, there are no unequivocal data on whether patients awaiting ablation or electric cardioversion should routinely undergo TOE, which is an invasive procedure that should be performed by trained and experienced personnel [11][12][13][14]. Risk stratification according to sex is common in clinical practice.…”
Section: Introductionmentioning
confidence: 99%